Measurement of Femoral Trochlear Morphology in Dogs Using Ultrasonography - Sasaki, Akari; Hidaka, Yuki; Mochizuki, Manabu; Honnami, Muneki (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to examine a method for measuring femoral trochlear morphology in dogs using ultrasonography, and survey femoral trochlear morphology in skeletally normal dogs.Study Design To examine the validity of ultrasonography, three raters measured the sulcus angle (SA; the angle between the medial and lateral facets) five times in five skeletally normal dogs. Intra- and interrater reliabilities were then calculated. We also calculated the correlation coefficient between SAs measured using ultrasonography and computed tomography (CT) or magnetic resonance imaging (MRI). Then, we surveyed the femoral trochlear morphology in skeletally normal dogs using ultrasonography.Results The intra- and interrater reliability for SAs measured using ultrasonography was good, and the correlation coefficient between SAs measured using ultrasonography and CT, or MRI, was strong. In skeletally normal dogs, the SAs for osseous contours decreased until 6 months of age. However, the SAs for cartilaginous contours did not change during the growth period.Conclusion The ultrasonographic measurement method is reliable for the evaluation of femoral trochlear morphology in dogs. The contour of the articular cartilage surface of the femoral trochlea is already determined early in life, and ossification of the articular cartilage of the femoral trochlea proceeds until 6 months of age. The results of this study will provide crucial information for the evaluation of femoral trochlear morphology in dogs.
Keywords: sulcus angle; dogs; femoral trochlea; patellar luxation; ultrasonography